Trait association and diversity in exotic lines of Indian mustard (Journal of Oilseed Brassica, 2026)
Total 41 exotic lines of Indian mustard (Brassica juncea L.) were evaluated during winter 2016-17 under irrigated environments. The genetic variability, heritability and genetic advance as percentage of mean for nine quantitative characters viz. plant height, number of primary branches number of primary branches, number of siliquae per plant, siliqua length (cm), number seeds per siliqua, number of seeds per plant, total seed yield (g) and test weight (g). Analysis of variance showed significant differences among the accession for all characters under study. Path coefficient analysis was carried out using correlation coefficients to know the yield contributing traits having true associations with seed yield. Improvement in seed yield can be achieved by selection using the correlation and path analysis data generated in this study. Total seed yield/ plant was positively correlated with siliqua length. Number of seeds/ plant and test weight had higher phenotypic direct effects on total seed yield/ plant, revealing that indirect selection for these traits would be effective in improving seed yield. The high heritability coupled with high genetic advance for test weight would also be of great use for indirect selection for improvement in seed yield. The material used in the study is of diverse nature and can be used in the breeding programme for development of improved genotypes in mustard.